CONDUCTING INDEPENDENT WORK FOR ESP STUDENTS IN CREDIT MODULE - Sobirova Robiyakhon; Akhmadaliyeva Feruzabonu (Scholar Express Journal, 2022)
Learning vocabulary is fundamental to support the learners to master English, because the ability of students to read and comprehend the subject material is relatively determined by their vocabulary. When the students have good vocabulary, they can understand paragraphs and texts better. Basically most learners know how important the words in a language is and they also realize that vocabulary learning strategies can be a very helpful device in their vocabulary learning journey. This article is about conducting Independent Work for ESP students in Credit Module
Keywords: Independence; second language; credit module; ESP